Recast Dreams: Class and Gender Consciousness in Steeltown - Rinehart, James (Labour / Le Travail, 1998)
The article reviews the book, "Recast Dreams: Class and Gender Consciousness in Steeltown," edited by D.W. Livingstone and J. Marshall Mangan.